Retrospective evaluation of the seasonality of canine tetanus in England (2006–2017): 49 dogs. Issue 4 (7th May 2021) - Starybrat, Daria; Burkitt‐Creedon, Jamie M.; Ellis, Jennifer; Humm, Karen
Abstract: Objective: To evaluate the seasonality of canine tetanus in England. Methods: Medical records of a single referral hospital in England were reviewed. Dogs diagnosed with localized or generalized tetanus between January 2006 and June 2017 were studied. Results: Forty‐nine cases were included. The prevalence of tetanus in England was significantly higher in the winter when compared with the summer ( P = 0.002) and autumn ( P = 0.024), with the highest number of cases recorded in February. Conclusions: The prevalence of canine tetanus in England was significantly higher in winter months, especially in February.